Trends of Energy Performance Certification of Buildings in Azerbaijan - Akbarova, Samira; ., . (International Journal of Engineering and Technology, 2018)
Energy consumption by construction sector is estimated by multi- disciplinary energy auditing and results are represented in an energy performance building certificate. The building certification, which is a world trend today, is applied successfully for many buildings  inAzerbaijantoo. The purpose of this paper to study the current methodology of energy building certification in terms of the technological aspects of energy auditing. Many documents of the European Union directives and Russian building codes and regulations in the field of ecology and energy saving in construction sector have been revised for implementing them as base for national energy performance certification system AZERI GREEN ZOOM. The assessment categories and main requirements have been considered. The results of this overview have shown the trends and problems in this field.  There are given examples of certified buildings.